Circulating neurodegeneration biomarkers neurofilament light protein and p‐tau181 are increased in individuals with heart failure at risk for vascular cognitive impairment. (20th December 2022) - Hoyer‐Kimura, Christina; Konhilas, John; Sweitzer, Nancy; Ryan, Lee; Hay, Meredith
Abstract: Background: Systemic inflammation, which is present in heart failure (HF), is known to increase risk for dementia and development of vascular cognitive impairment and dementia (VCID). Both neurofilament light protein (NfL) and tau phosphorylated at threonine‐181 (p‐tau181) are well known biomarkers of neurodegeneration in both Alzheimer's disease and non‐Alzheimer's disease neurodegenerative diseases. The purpose of the present study was to determine if blood levels of NfL and p‐tau181 are increased in HF patients at risk for VCID. Method: We performed a retrospective study of 58 participants from the previously completed TOPCAT trial (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist). TOPCAT participants had symptomatic HF categorized using New York Heart Association (NYHA) criteria, were > 50 years of age, and had ejection fraction (LVEF) ≥45%, assessed within 6 months from study start (n=58, 52% female). Control serum samples were obtained from age‐matched adults between 50‐85 with no known health issues (n=24, 50% female). NfL was measured using Simoa Quanterix and p‐Tau181 measured with SimoaHuman pTau‐181 V2 kit. Statistical analysis was performed using GraphPad and significance tested using Welch's ANOVA, Dunnett's post. Result: Baseline NfL levels were significantly higher in NYHA class I/II (n=56) and III/IV (n=54, p<.0001) than measured in age‐matched controls (see table for values). Over 12‐months follow‐up, participants in NYHA class I/II had an increase in NfL of 9.6±5% relative to baseline and those in class III/IV had a 31.7±17% increase from baseline. P‐tau181 levels were also significantly higher in both NYHA class I/II (n=56) and III/IV (n=54, p=.0002) as compared to age‐matched controls (see table for values) with levels were significantly higher in class III/IV than in class I/II participants (ANOVA, Dunnett's post, p<.001). Levels of p‐tau181 did not show significant changes over the 12‐month time in any group. Conclusion: These results demonstrate that 2 well‐studied biomarkers of neurodegeneration, NfL and p‐tau181, are elevated in subjects with HF. Studies are underway to determine if biomarker levels correlate with measures of cognitive function and MRI measures of brain structure and function in HF patients. (Supported by NIA U01AG066623).